Socio-economic Changes of Women through Kudumbasree – A Study from Puthenvelikkara (Gp) of Kerala State, India - Kenneth Kalyani and Seena P.C (International Research Journal of Social Sciences, 2012)
Kudumbashree is a multi-faceted women based participatory poverty eradication programme jointly initiated by Government of Kerala and NABARD. It is implemented by community based organizations (CBOs) of poor women in co-operation with Local Self Government Institutions. Mission of Kudumbasree: “To eradicate absolute poverty in ten years through concerted community action under the leadership of local governments, by facilitating organisation of poor for combining self help with demand led convergence of available services and resources to tackle the multiple dimensions and manifestation of poverty holistically”. Reaching out to the families through women and reaching out to the society through families. In this manuscript the author made an indebt exploration of the various programmes that were introduced in order to enhance and empower the women from the below poverty line of puthanvelikkara gram panchayath of Ernakulum District of Kerela state. Self prepared questionnaire is administered among them to assess their socio economic development after the participation in Kudumbasree. The finding reveal that economic development is the base for other development. Collective effort has been recognized as tenets of women empowerment, women empowerment leads to sustainable social development, Economic development of women leads to better living status in the family, educational, nutritional, and the health needs of the children were well satisfied and economic independence through kudumbasree improved the social participation of its members.